Atom Resolved Surface Reactions ; Nanocatalysis - Davies, P. R. (Philip Rosser), 1964- (RSC nanoscience & nanotechnology., 2007)
This book offers a unique perspective of the impact of scanning probe microscopies on our understanding of the surface chemistry at the nanoscale.